Growth and Wood Traits of Plantation Grown Acacia mangium, A. auriculiformis and A. crassicarpa from Thane, Maharashtra - Varghese, Mohan; Nicodemus, A.; Subramanian, K. (Indian Forester, 1999)
Acacia auriculiformis is one of the Australian Acacia species introduced in India for afforesting degraded lands, meeting fuelwood needs and as avenue trees. This species has been raised in the Western Ghats areas of Maharashtra and found to be very successful. Efforts were made to introduce A. mangium and A. crassicarpa by procuring seeds from Australia and Thailand. Growth performance and wood characteristics were studied in A. mangium, A. auriculiformis and A. crassicarpa planted in Thane District of Maharashtra. A. mangium had better growth than A. auriculiformis and A. crassicarpa. A. auriculiformis had higher wood density and phyllode index than the other species and A. Crassicarpa had long fibres and vessel elements. Since A. Mangium is being increasingly planted in tropical countries, multi-locational trials need to be raised in high rainfall areas in India to select the best performing seedlots.